Root causes and improvement proposals for cost overrun in projects: A contractor's perspective - Lutz, Tobias (My University, 2020)
Project costs tend to overrun, regardless of the size and type of the project. Research has shown that little progress has been made in this field. The problem also applies to contractors, which repeatedly struggle to stay on budget and therefore face cost overruns in their projects. This study aims to locate the root causes of cost overrun in the projects of the case company, which is a global technology company. Moreover, areas for improvement are proposed for the mitigation of future cost overruns. To do so, several theories and methodologies are applied: The RAL concept, the Analytical Hierarchy Process, the Critical Factor Indexes, the Sense and Respond methodology, the Manufacturing Strategy Index, the Sustainable Competitive Ad-vantage method, and Knowledge and Technology. Two questionnaires were used for the data collection and were answered by a total of 18 respondents. Besides, interviews were carried out to get background information and to validate the results with the Weak Market Test. This study focuses on the engineering process and the site management process of the projects, which contribute the most to the cost overruns of the case company. Challenges in resource management and the cooperation with the client were found to be the root causes of cost overrun in the examined projects. To mitigate future cost overruns, it was proposed to lay a special focus on Project Scheduling, Basic Design, Detailed Design, and Off-site Validation. Moreover, improvements in Resource Management, uniform working directives, and special attention to new clients and clients with consultants contribute to the mitigation of future cost overruns. The Knowledge and Technology results indicate that the products and services of the case company are in the maturity phase of the technology life cycle. Thus, a reduction in production costs is suggested. The highest uncertainty is related to core technology, hence investments in core technology will further contribute to the success of future projects.
Keywords: costs; project management; competitive advantage; industrial management; knowledge management; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management